Case studies in mechanical engineering : decision making, thermodynamics, fluid mechanics and heat transfer - Sabol, Stuart (Chichester, West Sussex, United Kingdom : John Wiley & Sons, Inc., 2016)
Using a case study approach, this reference tests the reader's ability to apply engineering fundamentals to real-world examples and receive constructive feedback Case Studies in Mechanical Engineering provides real life examples of the application of engineering fundamentals. They relate to real equipment, real people and real decisions. They influence careers, projects, companies, and governments. The cases serve as supplements to fundamental courses in thermodynamics, fluid mechanics, heat transfer, instrumentation, economics, and statistics. The author explains equipment and concepts to solve the problems and suggests relevant assignments to augment the cases. Graduate engineers seeking to refresh their career, or acquire continuing education will find the studies challenging and rewarding. Each case is designed to be accomplished in one week, earning up to 15 hours of continuing education credit. Each case study provides methods to present an argument, work with clients, recommend action and develop new business. Key features: -Highlights the economic consequences of engineering designs and decisions. -Encourages problem solving skills. -Application of fundamentals to life experiences. -Ability to practice with real life examples. Case Studies in Mechanical Engineering is a valuable reference for mechanical engineering practitioners working in thermodynamics, fluid mechanics, heat transfer and related areas.
Steam Turbine Performance Degradation -- Risk/Reward Evaluation -- Gas Turbine Compressor Fouling -- Flow Instrument Degradation, Use and Placement -- Two-Phase Hydraulics -- Reliability and Availability -- Efficiency and Air Emissions -- Low-Carbon Power Production -- Heat Exchangers and Drain Line Sizing -- Optimized Maintenance -- Project Engineering -- In the Woodshop.
Includes bibliographical references and index.
Print version record.
Keywords: Mechanical engineering -- Case studies; Mechanics, Applied -- Problems, exercises, etc; Dynamics -- Problems, exercises, etc; TECHNOLOGY & ENGINEERING / Mechanical; Dynamics; Mechanical engineering; Mechanics, Applied; Electronic books; Case studies; Problems and exercises